2008
DOI: 10.1016/j.immuni.2008.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-23 Restrains Regulatory T Cell Activity to Drive T Cell-Dependent Colitis

Abstract: SummaryInterleukin-23 (IL-23) is an inflammatory cytokine that plays a key role in the pathogenesis of several autoimmune and inflammatory diseases. It orchestrates innate and T cell-mediated inflammatory pathways and can promote T helper 17 (Th17) cell responses. Utilizing a T cell transfer model, we showed that IL-23-dependent colitis did not require IL-17 secretion by T cells. Furthermore, IL-23-independent intestinal inflammation could develop if immunosuppressive pathways were reduced. The frequency of na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
349
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 367 publications
(373 citation statements)
references
References 55 publications
21
349
0
3
Order By: Relevance
“…In an infection model, IL-23 was found to be dispensable for the generation of IL-17-producing T cells, but was essential for schistosome egg-induced immunopathology [84]. This is consistent with a recent study on colitis, which demonstrated that IL-17-producing T cells are not required for the development of intestinal inflammation, but that IL-23 does have a pathogenic role by inhibiting Treg cells [85], and thereby enhancing Th1 responses. It has also been demonstrated that IL-23, as well as promoting IL-17 producing T cells, can enhance IFN-g-producing Th1 cells [62].…”
supporting
confidence: 87%
“…In an infection model, IL-23 was found to be dispensable for the generation of IL-17-producing T cells, but was essential for schistosome egg-induced immunopathology [84]. This is consistent with a recent study on colitis, which demonstrated that IL-17-producing T cells are not required for the development of intestinal inflammation, but that IL-23 does have a pathogenic role by inhibiting Treg cells [85], and thereby enhancing Th1 responses. It has also been demonstrated that IL-23, as well as promoting IL-17 producing T cells, can enhance IFN-g-producing Th1 cells [62].…”
supporting
confidence: 87%
“…Naïve CD4 1 CD45RB high T cells were isolated from spleens of B6 or BALB/c mice via FACS sorting as previously described [22]. Rag À/À mice were then i.p.…”
Section: Induction Of Colitismentioning
confidence: 99%
“…Analysis of ALDH activity was performed using the ALDEFLUOR staining kit according to manufacturer's instructions (STEMCELLS Technologies). Foxp3 staining as well as the analysis of intracellular cytokines was performed as described elsewhere [22]. Data were collected with a Cyan flow cytometer (Dako) and analysed using FlowJo software (Tree star).…”
Section: Isolation Of Leukocytes and Flow Cytometry Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Les choses ne sont toutefois peut-être pas si simples. Ainsi, si il est maintenant acquis que l'IL-23 joue un rôle déterminant dans le développement des maladies inflammatoires du tube digestif chez l'homme comme chez l'animal [8], une étude récente mené chez la souris a montré que cette cytokine exercerait son effet délétère, non pas en favorisant l'expansion ou l'activité des lymphocytes Th17, mais plutôt en exerçant un effet inhibiteur sur les lymphocytes T régulateurs [9].…”
Section: Un Rôle Encore Incertain Des Lymphocytes Th17 Dans Les Maladunclassified